Analysis of The Relationship Between Electricite Du Laos Generation Public Company’s Stock Price and The Gold Price in the National Market - HONGSOULYYANG, Mee; XIONGTOUA, Tongvang; CHANTHAVONE, Thongphanh; KINGSADA, Youtthasack; SYVILAISITH, Toukta (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Analysis of the relationship between The Eletricite Du Laos (EDL) Generation Public Company’s stock price and the gold price in the international market has applied the real price of stock from Lao Security Exchange’s website and the gold price from World Bank’s website during 2011-2018. The study found out that: The Volatility of the EDL-Generation Public Company’s stock price is 0.17 and the volatility of the gold price in the international market is 0.12. This infers that the volatility of EDL- Generation Public Company’s is larger than the volatility of the gold price in international market. This shows that the stock price’s fluctuation of the EDL Public Company is bigger than the stock price of the international market. The EDL-Generation Public Company’s stock price and the gold price in the international market have negative relationship with the significant value of 0.01. When the international market’s gold price raises by 1 unit, the EDL-Generation Public Company’s stock price would decline by 0.000703 units. On the contrary, if the international market’s gold price decrease by 1 unit, the EDL-Generation Public Company’s stock price would raise by 0.000703 units with the significant value of 0.01. The appropriate regression model is R2 = 0.684481 or2 = 68.44 %. It means that the international market’s gold price has an influence to the EDL-Generation Public Company’s stock price by 68.44% and other influences are from other factors. In conclusion of cause and effect, the change of the gold price in the international market makes a change in the stock price of the EDL-Generation Public Company with the significant of 0.1. But the changes in the stock price of the EDL-Generation Public Company make no change of the gold price in the international market.